PENGARUH PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP BELANJA MODAL SERTA HUBUNGANNYA DENGAN PENDAPATAN PERKAPITA (PDRB PERKAPITA) PADA KABUPATEN/KOTA DI PROPINSI JAWA TENGAH TAHUN 2007 - 2011 - Karmani, 11.4202.0026 (Students Journal of Economic and Management, 2013)
The implementation of regional autonomy are basicaly local independence, which is characterized by the ability of local governments to manage taxes and levies. The results of tax revenues and user fees are used to funding local development, which directly and indirectly affect the welfare of society. This research aims to know the influence of the local taxes, levies and capital expenditures per capita income in the municipality in Central Java Province The data was used in this research is secondary data, ie data taxes and levies, capital expenditure data were sourced from the the Ministry of Finance, and per capita income data sourced from the Central Statistical Office Â of Central Java The results of the analysis was known that the regional tax and levies had positive impact on capital spending. Local taxes is also had a positive impact on per capita income, while the levies and capital expenditures have a negative effect on income per capita Â  Keywords: Local Taxes, Levies, capital expenditures and income per capita